Blood Flow Restriction Training Blunts Chronic Kidney Disease Progression in Humans. Issue 2 (February 2021) - Corrêa, Hugo Luca; Neves, Rodrigo Vanerson Passos; Deus, Lysleine Alves; Souza, Michel Kendy; Haro, Anderson Sola; Costa, Fernando; Silva, Victor Lopes; Santos, Claudio Avelino Rodrigues; Moraes, Milton Rocha; Simões, Herbert Gustavo; Navalta, James Wilfred; Prestes, Jonato; et al.
ABSTRACT: Purpose: This study aimed to verify the effect of 6 months of periodized resistance training (RT) with and without blood flow restriction (BFR) in patients with stage 2 chronic kidney disease (CKD) on glomerular filtration rate (GFR), uremic parameters, cytokines, and klotho–fibroblast growth factor 23 (FGF23) axis. Methods: A total of 105 subjects were randomized in three groups of 35 each: control (CTL), RT, and RT + BFR. A first visit was required for an anamnesis to evaluate the number of medications and anthropometric measurements (body weight, height, and body mass index). Muscle strength (one-repetition maximum) was assessed. Venous blood samples were collected at baseline and after 6 months of training in all patients for the analysis of markers of renal function and integrity, as well as for the determination of the inflammatory profile. Statistical significances were adopted with P < 0.05. Results: Both training therapies attenuated the decline of GFR ( P < 0.05). The majority of CTL patients declined to stage 3 CKD (88.5%), whereas fewer incidents were noted with RT (25.7%) and RT + BFR (17.1%). Improved uremic parameters as well as inflammation (IL-6, IL-10, IL-15, IL-17a, IL-18, and TNF-α) and klotho–FGF23 axis in RT and RT + BFR ( P < 0.05) were observed. Monocyte chemoattractant protein 1 was not changed ( P > 0.05) but presented a large effect size (Cohen's d ), demonstrating a propensity for improvement. Conclusion: Six months of periodized RT with and without BFR in patients with stage 2 CKD attenuated the progression of the disease by maintaining GFR, improving uremic parameters, cytokine profile regulation, and klotho–FGF23 axis. Abstract : Supplemental digital content is available in the text.